HIV Community Viral Load and Factors Associated With Elevated Viremia Among a Community-Based Sample of Men Who Have Sex With Men in Vancouver, Canada. (1st May 2016) - Moore, David M.; Cui, Zishan; Lachowsky, Nathan; Raymond, Henry F.; Roth, Eric; Rich, Ashleigh; Sereda, Paul; Howard, Terry; McFarland, Willi; Lal, Allan; Montaner, Julio; Corneil, Trevor; et al.
Abstract : Background: We developed estimates of community viral load (VL) and risk factors for unsuppressed VL from a cross-sectional study of men who have sex with men (MSM) in Vancouver, Canada. Methods: MSM were recruited from February 25, 2012 to February 28, 2014 using respondent-driven sampling (RDS). Participants completed a computer-assisted self-interview questionnaire and a nurse-administered point-of-care HIV test. For HIV-positive participants, we conducted VL and CD4 cell counts. We used RDS-weighted analysis to obtain population estimates of key variables and multivariable logistic regression to examine factors associated with having a VL of ≥200 copies per milliliter among HIV-positive participants. Results: We recruited 719 participants, of whom 119 (16.6%) were seeds. Our estimate of the population prevalence of HIV was 23.4% [95% confidence interval (CI): 15.8% to 31.0%] after RDS adjustments. We estimated that 18.6% (95% CI: 8.8% to 30.4%) of HIV-positive MSM in Vancouver had a VL of ≥200 copies per milliliter. Having an unsuppressed VL was associated with non-white ethnicity [adjusted odds ratio (AOR) = 4.34; 95% CI: 1.67 to 11.1], an annual income of <$15, 000 CAD (AOR = 6.43; 95% CI: 2.08 to 19.9), using gamma-hydroxy butyrate in the previous 6 months (AOR = 4.85; 95% CI: 1.79 to 13.2), unprotected anal intercourse with a known HIV-negative or an unknown serostatus partner (AOR = 3.13; 95% CI: 1.10 to 8.90), and disclosing one's HIV serostatus ≥50% of the time (AOR = 7.04; 95% CI: 1.01 to 49.1). Conclusion: Despite a high prevalence of HIV, we estimated that a small proportion of HIV-positive MSM have undiagnosed HIV and unsuppressed VL. Our results highlight the importance of continued work to address health inequities using a framework based on social determinants of health.